Comparing anesthesia modes in major burns: Total intravenous anesthesia versus general anesthesia - A cross-sectional study in a Central Indian government hospital - Shalini Jain,; Shivram, Nandita; Sachin Verma,; Arora KK, (Asian Journal of Medical Sciences, 2023)
Background: Burn injuries remain a significant public health concern, causing complex trauma. Early excision and skin grafting are standard in burn management to reduce infection and scarring. The choice of anesthesia is critical for optimal pain control and hemodynamic stability. Aims and Objectives: This study aims to compare total intravenous anesthesia (TIVA) and general anesthesia (GA) in patients of major burns. Materials and Methods: The study was conducted in the Department of Anaesthesia, M.G.M. Medical College and M.Y. Hospital, Indore, over a period of 12 months. One hundred and twenty patients with 10–12% total burn area were included and randomized into two groups of 60 patients each. Group T patients received TIVA and Group G patients received GA. Results: Both the groups were comparable with respect to age, gender, and baseline vitals. The mean heart rate, systolic and diastolic blood pressure, and mean MAP were significantly higher in Group G at 0, 30, and 60 min. In Group T, all patients achieved an Aldrete score of 9 or more within 10 min. Pain was more prevalent in Group G patients, and the comparison was found to be statistically significant. The mean time to first rescue analgesia in Group T was later than Group G, and the difference was found to be statistically significant. Conclusion: From the results, we may conclude that TIVA provides superior hemodynamic stability, shorter post-anesthesia unit recovery time, and improved analgesia compared to GA. However, there are lacunae in the literature, hence we recommend that larger studies comparing these two anesthesia modes be conducted before generalizing the present findings to the general population.